A human antibody specific for SIRPα reprograms macrophages and promotes antibody mediated anti-cancer activity - Keifer G. Kurtz; Irina Lebedeva; Stephanie A. Pierre; David Andrew; Yu-Rou Liao; Daisy Ambriz; Olivia Vergnolle; Leyi Shen; Elizabeth Nyakatura; Manuel Baca; David A. Scheinberg (PLoS ONE, 2025)
Several T cell immune checkpoint blockade therapies have shown initial successes in multiple cancers. However, significant issues remain, including tumor relapse, severe toxicities, and a lack of efficacy in most patients. SIRPα, commonly known as the “do not eat me signal”, is a monocyte checkpoint cell surface protein. Agents that block the interaction of CD47 with SIRPα have recently shown clinical success in combination with monoclonal antibody therapy to potentiate macrophage phagocytosis of tumors. However, significant toxicities and logistical issues are associated with CD47-targeted agents due to the expression of CD47 on all human cells. In contrast, SIRPα has expression limited to myelomonocytic cells, meaning highly specific SIRPα blocking agents might reduce these toxicities and avoid the target antigen sink. Herein, we generated a high affinity and highly specific SIRPα-targeting monoclonal antibody, F05, that has enhanced SIRPα binding and reduced SIRPβ and SIRPγ binding capacity when compared to other available SIRPα antibodies. Furthermore, we show F05 reprograms immunosuppressive macrophages toward a phagocytic profile in vitro. F05 demonstrated efficacy in solid tumor animal models, providing a rationale for further development of the antibody.